Exploring the Relationship between Broadband and Economic Growth - Minges, Michael (World Bank, Washington, DC, 2016)
This paper first looks at different studies on the economic impact of broadband illustrating the range of models and data that have been used. It then examines some of the issues that complicate the task of gauging how broadband impacts the economy. The paper concludes with a summary of the key results and suggestions for moving forward.